Scc2/Nipbl hops between chromosomal cohesin rings after loading - James Rhodes; Davide Mazza; Kim Nasmyth; Stephan Uphoff (eLife, 2017)
The cohesin complex mediates DNA-DNA interactions both between (sister chromatid cohesion) and within chromosomes (DNA looping). It has been suggested that intra-chromosome loops are generated by extrusion of DNAs through the lumen of cohesin’s ring. Scc2 (Nipbl) stimulates cohesin’s ABC-like ATPase and is essential for loading cohesin onto chromosomes. However, it is possible that the stimulation of cohesin’s ATPase by Scc2 also has a post-loading function, for example driving loop extrusion. Using fluorescence recovery after photobleaching (FRAP) and single-molecule tracking in human cells, we show that Scc2 binds dynamically to chromatin, principally through an association with cohesin. Scc2’s movement within chromatin is consistent with a 'stop-and-go' or 'hopping' motion. We suggest that a low diffusion coefficient, a low stoichiometry relative to cohesin, and a high affinity for chromosomal cohesin enables Scc2 to move rapidly from one chromosomal cohesin complex to another, performing a function distinct from loading.